PENYUSUNAN AD/ART UNTUK MENDUKUNG KEPEMIMPINAN KOLEKTIF DI KOMUNITAS ATMA RIDERS - Fathiyyah Zalfaa; Nasya Prilita Prihandono; Daria Develle Veronica Manalu; Lauren Yusmita Danela Siburian; Sabina Citra Narindra; Penny Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2026)
Atma Riders is a motorcycle enthusiast community within Atma Jaya Catholic University of Indonesia that emphasizes family values and collective leadership. However, the community has faced several internal challenges, including the absence of a clear organizational system, low member participation, weak coordination among divisions, and conflicts caused by unclear roles and decision-making mechanisms. This community engagement program aimed to develop participatory and flexible Bylaws (AD/ART) that align with the community’s characteristics to support organizational sustainability. The program employed a Participatory Action Research (PAR) approach through several stages, including need assessment, focus group discussions (FGDs), workshops for drafting the bylaws, and program evaluation. The intervention involved active board members, community members, alumni, faculty advisors, and a law student who supported the legal drafting process. The results demonstrated that the collaborative development of the AD/ART successfully clarified the organizational structure, role distribution, members’ rights and obligations, as well as conflict resolution and decision-making mechanisms. Program evaluation based on Dunn’s dimensions indicated positive outcomes in effectiveness, adequacy, responsiveness, and appropriateness. Furthermore, the participatory process enhanced members’ sense of ownership, emotional attachment to the community, and commitment to implementing collective leadership practices. The resulting AD/ART serves not only as a formal organizational document but also as a strategic foundation for strengthening collective leadership, transparency, and the long-term sustainability of the Atma Riders community. ABSTRAK Komunitas Atma Riders merupakan komunitas pecinta motor di lingkungan Universitas Katolik Indonesia Atma Jaya yang mengedepankan nilai kekeluargaan dan kepemimpinan kolektif. Namun, komunitas ini menghadapi berbagai permasalahan internal, seperti belum adanya sistem organisasi yang jelas, rendahnya partisipasi anggota, lemahnya koordinasi antar divisi, serta konflik akibat ketidakjelasan peran dan mekanisme pengambilan keputusan. Kegiatan pengabdian kepada masyarakat ini bertujuan menyusun Anggaran Dasar dan Anggaran Rumah Tangga (AD/ART) yang partisipatif, fleksibel, dan sesuai dengan karakter komunitas untuk mendukung keberlanjutan organisasi. Program dilaksanakan menggunakan pendekatan Participatory Action Research (PAR) melalui tahapan need assessment, focus group discussion (FGD), workshop penyusunan AD/ART, serta evaluasi program. Intervensi melibatkan pengurus aktif, anggota, alumni, dosen pendamping, dan mahasiswa hukum sebagai pendukung penyusunan dokumen. Hasil kegiatan menunjukkan bahwa penyusunan AD/ART secara kolaboratif berhasil memperjelas struktur organisasi, pembagian peran, hak dan kewajiban anggota, serta mekanisme penyelesaian konflik dan pengambilan keputusan. Evaluasi program berdasarkan dimensi Dunn menunjukkan hasil yang baik pada aspek efektivitas, kecukupan, responsivitas, dan ketepatan. Selain itu, proses partisipatif meningkatkan rasa memiliki (sense of ownership), keterikatan anggota terhadap komunitas, dan komitmen untuk menjalankan organisasi secara kolektif. Penyusunan AD/ART ini tidak hanya berfungsi sebagai dokumen formal organisasi, tetapi juga menjadi fondasi strategis dalam memperkuat kepemimpinan kolektif, transparansi, dan keberlanjutan komunitas Atma Riders di masa mendatang.